2021
DOI: 10.18176/jiaci.0478
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Disease Management in Adult Patients With Atopic Dermatitis Receiving Care at Reference Hospitals in Brazil: the ADAPT Study

Abstract: Background: Atopic dermatitis is a chronic inflammatory skin disease with a prevalence of 0.02% to 8.1% in adults. Adult patients with moderate-to-severe atopic dermatitis have frequent relapses and significant disease burden.Objectives: Characterize clinical, immunological and therapeutic features of Brazilian adults with atopic dermatitis.Methods: A multicenter, observational, retrospective, descriptive registry-based study, conducted at reference hospitals, between December 2016 and October 2017. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…While the pathogenesis of AD is linked to genetic factors, environmental factors such as air pollution and aeroallergens (e.g., pet hair, house dust mite, and pollen) may give rise to the growth of the incidence rate. Furthermore, stratum corneum wall could be damaged by altering lifestyles including frequently utilizing soap or staying a long time in air-conditioned room [23]. Thus, the average age of beginning of AD disease is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…While the pathogenesis of AD is linked to genetic factors, environmental factors such as air pollution and aeroallergens (e.g., pet hair, house dust mite, and pollen) may give rise to the growth of the incidence rate. Furthermore, stratum corneum wall could be damaged by altering lifestyles including frequently utilizing soap or staying a long time in air-conditioned room [23]. Thus, the average age of beginning of AD disease is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluating one-year prevalence of AD in Brazil through a population-based telephone survey, revealed that the age-adjusted prevalence of AD was 2.27% [9]. Data on the epidemiology of adult AD in Latin America are extremely limited, with one multicenter retrospective study in Brazil named ADAPT SA, a multicentric, non-interventional study to describe clinical features and disease management of adult patients with atopic dermatitis followed at tertiary hospitals [10].…”
Section: Epidemiology Of Admentioning
confidence: 99%
“…The Brazilian ADAPT study analyzed the clinical characteristics of AD and found that most patients presented with flexural lesions in the popliteal and antecubital regions, and lesions distributed on extensor surfaces such as the extremities and trunk [10]. At the first visit, the main AD reported features were erythema (54.5%), pruritus (55.1%), and dry skin (48.7%), and lesions had the characteristic lichenified or eczematous morphology [10]. In a cohort of 1,650 Argentinian patients with AD, 40% experienced high itch intensity and frequency, and 96% reported bleeding and suppuration [24].…”
Section: Clinical Characteristics Impact On Quality Of Life and Ad As...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Colombia and Brazil suggest a lower response to topical and systemic treatment in severe disease [44,45], and other LA studies suggest that comorbidities are linked to increased severity [13,14,46]. Control parameters such as QoL, disease persistence, and improvement of physical and mental comorbidities have not been studied adequately in LA.…”
Section: Ad Control In Lamentioning
confidence: 99%